Purification and characterization of isoforms of glutathione S-transferase (GST) from Acinetobacter Calcoaceticus Y1 / Chee Chin Soon - Chee, Chin Soon (2014)
Bacteria were isolated from chemically-contaminated soil and the isolates were screened for glutathione S-transferase (GST) expression by spraying with monochlorobimane. The isolate with the most promising GST activity was later identified as Acinetobacter calcoacticus Y1 based on its 16S rRNA gene sequence. By using affinity chromatography, A. calcoaceticus Y1 putative GST (AcGST) was successfully purified and expressed GST subunit with molecular weight estimated at 23 kDa when analysed on sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). The purified protein was then further analysed by using two-dimensional electrophoresis where two putative GST isozymes were identified and designated as AcGST-1 and AcGST-2. Upon isoelectric focusing, AcGST-1 and AcGST-2 were found to be in pI values of 4.5 and 6.2 respectively. AcGST-1 and AcGST-2 were purified by using carboxylmethyl (CM) and diethylaminoethyl (DEAE) ion exchange chromatography respectively. AcGST-1 was reactive towards ethacrynic acid (EA) (24.99 ± 1.24 μmol/min/mg), hydrogen peroxide (3.93 ± 0.32 μmol/min/mg), 1-Chloro-2,4-dinitrobenzene (CDNB) (0.61 ± 0.12 μmol/min/mg), 2,4-heptadienal (0.11 ± 0.03 μmol/min/mg), trans-2-octenal (0.08 ± 0.02 μmol/min/mg), and hexadienal (0.04 ± 0.003 μmol/min/mg) whereas AcGST-2 was reactive towards EA (15.87 ± 2.54 μmol/min/mg ), CDNB (0.54 ± 0.13 μmol/min/mg), 2,4-heptadienal (0.08 ± 0.01 μmol/min/mg), and trans-2-octenal (0.09 ± 0.01 μmol/min/mg). The substrate specificities of both putative GST isozymes were different and therefore suggesting they were of two existing homodimers. For AcGST-1, the Vmax for EA and GSH were estimated as 3.74 ± 1.40 μmol/min and 1.46 ± 0.02 μmol/min, Km for EA and GSH were estimated as 0.28 ± 0.02 mM and 0.01 ± 0.0003 mM. Whereas for AcGST-2, the Vmax for EA and GSH were estimated as 8.41 ± 1.08 μmol/min and 1.35 ± 0.01 μmol/min, Km for EA and GSH were estimated as 0.28 ± 0.002 mM and 0.02 ± 0.003 mM. From thin layer chromatography to determine the reactivity of both putative GST isozymes towards Isoproturon, Fenoxaprop-ethyl, Propoxur and Clodinafop-propargyl, only AcGST-2 showed conjugation activity towards Isoproturon, a pesticide. Disc diffusion test indicated that Bromophos, Malathione, DDT, Propoxur, Permethin, Chlorpyrifos, Fenitrothion did not affect the propagation of A. calcoaecticus Y1 but hydrogen peroxide inhibited the propagation of A. calcoaceticus Y1. Based on our result, zone of inhibition at 25 % of hydrogen peroxide was smaller compared with 50 % of hydrogen peroxide suggesting some degree of tolerance of A. calcoaceticus Y1 towards hydrogen peroxide.